2020
DOI: 10.1002/adma.201908109
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally Synchronous Oxygen Self‐Supply and Reactive Oxygen Species Production on Z‐Scheme Heterostructures for Hypoxic Tumor Therapy

Abstract: Photodynamic therapy (PDT) efficacy has been severely limited by oxygen (O2) deficiency in tumors and the electron–hole separation inefficiency in photosensitizers, especially the long‐range diffusion of O2 toward photosensitizers during the PDT process. Herein, novel bismuth sulfide (Bi2S3)@bismuth (Bi) Z‐scheme heterostructured nanorods (NRs) are designed to realize the spatiotemporally synchronous O2 self‐supply and production of reactive oxygen species for hypoxic tumor therapy. Both narrow‐bandgap Bi2S3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 52 publications
0
103
0
Order By: Relevance
“…Reproduced with permission. [22] Copyright 2020, Wiley-VCH. et al later demonstrated a new system to explore OERbased watersplitting for hypoxiaovercoming PDT.…”
Section: Oer-enriched Pdtmentioning
confidence: 99%
“…Reproduced with permission. [22] Copyright 2020, Wiley-VCH. et al later demonstrated a new system to explore OERbased watersplitting for hypoxiaovercoming PDT.…”
Section: Oer-enriched Pdtmentioning
confidence: 99%
“…Typically, DPBF was used as a probe molecule to detect the singlet oxygen generation of different samples [35]. 1 mL of ICG@FeDH aqueous solution at concentration of 100 μg/mL was mixed with 50 μL of DPBF dissolved in dimethyl sulfoxide (10 mM) and irradiated by a 808 nm laser (1 mW/cm 2 ).…”
Section: Reactive Oxygen Species Detectionmentioning
confidence: 99%
“…Apoptosis is one of the main ways in inhibiting the growth of tumor cells, and mitochondria are the most important organelles in the regulation of this process [33]. In addition to supplying energy to cells, mitochondria produce ROS, an apoptosisinducing signal molecule [34]. ROS can directly trigger the opening of mitochondrial permeability transition pores and decrease the mitochondrial membrane potential, resulting in the activation of the mitochondrial Caspase-dependent apoptosis pathway [35,36].…”
Section: Anti-lymphoma Mechanism Of Ccm@msns-isoimmentioning
confidence: 99%